2020
DOI: 10.1016/j.redox.2020.101654
|View full text |Cite|
|
Sign up to set email alerts
|

Genome-wide transcriptional effects of deletions of sulphur metabolism genes in Drosophila melanogaster

Abstract: In recent years, the gasotransmitter hydrogen sulphide (H 2 S), produced by the transsulphuration pathway, has been recognized as a biological mediator playing an important role under normal conditions and in various pathologies in both eukaryotes and prokaryotes. The transsulphuration pathway (TSP) includes the conversion of homocysteine to cysteine following the breakdown of methionine. In Drosophila melanogaster and other eukaryotes, H 2 S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 100 publications
(139 reference statements)
0
12
0
Order By: Relevance
“…H 2 S can inhibit mitochondrial function and depress cellular oxygen receptors to reduce the metabolic demand for oxygen. [201][202][203][204][205][206] Blackstone et al demonstrated that 80 ppm of H 2 S suppress metabolism in mice, causing them to enter a hibernation state. [70] However, Drabek et al reported that intravenous H 2 S failed to improve the survival rate of pigs with hemorrhagic shock.…”
Section: Metabolic Suppressionmentioning
confidence: 99%
“…H 2 S can inhibit mitochondrial function and depress cellular oxygen receptors to reduce the metabolic demand for oxygen. [201][202][203][204][205][206] Blackstone et al demonstrated that 80 ppm of H 2 S suppress metabolism in mice, causing them to enter a hibernation state. [70] However, Drabek et al reported that intravenous H 2 S failed to improve the survival rate of pigs with hemorrhagic shock.…”
Section: Metabolic Suppressionmentioning
confidence: 99%
“…Recently, it has been shown that H 2 S is involved in the regulation of the chaperone function. Enzymes controlling the H 2 S production CSE/CTH/CGL (cystathionine-γ lyase), CBS (cystathionine-β-synthase), and MST (3-mercaptopyruvate sulfurtransferase) are implicated in stress resistance, aging, and stress-dependent regulation of HSP22, HSP70, and HSF1 [ 87 , 88 ]. Chaperones play an important role in adaptive stress and can directly regulate the expression of the Foxo3 gene associated with lifespan (Forkhead box O3) [ 89 ].…”
Section: Age-related Changes In Plasma Biochemistry and Vascular Dmentioning
confidence: 99%
“…However, to the best of our knowledge, there are only scattered data implicating the synthesis of endogenous H 2 S in the memory process and mating behavior under normal conditions in higher organisms [ 21 , 22 ]. Drosophila melanogaster strains obtained in our laboratory [ 23 ] containing single and double deletions of the three major genes implicated in H 2 S production represent a convenient model to study the role of H 2 S production in learning and memory processes in higher organisms.…”
Section: Introductionmentioning
confidence: 99%
“…In the experiments described herein, we made use of several D. melanogaster strains obtained using the CRISPR/Cas9 technique. These strains with deletions of the three genes ( CBS, CSE, and MST ) were used and described in detail in our previous studies [ 23 , 28 ]. Transcriptomic studies demonstrated that the deletions of both CBS and CSE ( CBS-/- ; CSE-/- ) have a cumulative effect and drastically alter genome expression, with a more pronounced impact exerted by the deletion of the CBS gene.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation